Tanggung Jawab Hukum Inventor Atas Invensi Kecerdasan Buatan (Artificial Intelligence) Di Indonesia - Putranti, Deslaely; Anggraeny, Kurnia Dewi (Jurnal Hukum & Pembangunan, 2022)
The pace of technological development can no longer be restrained until the emergence of artificial intelligence (AI) which later, turns out to have a negative impact on its application. AI is a computer system program created by humans. However, the invention of AI in one hand makes human work easier, it is also noticeable that there are several criminal cases "performed" by AI. This research is qualitative research with doctrinal research. The data used include secondary data consisting of primary, secondary and tertiary legal materials. The method of data collection is done through document study. This research concludes that the inventor of an invention of artificial intelligence can be charged with legal responsibility by applying the limits of liability both in civil and penal sanction. Further studies are needed to be able to answer the question of how far this responsibility can be carried out.